Pasting properties of teff, maize, and potato starches with added microcrystalline cellulose and cellulose nanofiber - Emmambux, Mohammad Naushad (University of Pretoria, 2022)
Dissertation (MSc (Food Sciences))--University of Pretoria, 2022.